Penyuluhan Hukum Peningkatan Kesadaran Hukum Pemenuhan dan Perlindungan Hak-Hak anak - Salam, Safrin; Nurcahyo, Edy; Kaswandi, Kaswandi; Fauzi, Ahmad; Salnaf Ituga, Rauf Akbar; Andi, Samsir (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Child protection aims to maintain and protect the dignity and rights of children so that they do not experience violence or discrimination. The method used in implementing this community service activity is focus group discussion (FGD). The results of community service show that children who are not yet 18 years old receive legal protection according to Law No. 35 of 2014. Then there also needs to be legal protection for teachers when teachers implement disciplinary sanctions against students who violate school rules. This legal education can be a guide for the government, schools, and parents in looking at cases of violence against children. The government can develop appropriate programmes to reduce the number of violent incidents among schoolchildren by strengthening the role of teachers and parents. Parents need to understand the legal principles of child protection, while teachers, as substitutes for second parents, need to receive legal protection as regulated by the w. Republic of Indonesia Number 14 of 2005 Concerning Teachers and Lecturers.